Strengthening scientific cooperation: Reducing marine pollution by at least 10% by 2030 in line with the 2020 - 2030 Agenda on the sustainable use of oceans, seas and marine resources - Cristiana Sîrbu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The paper presents, with examples, the steps through which scientific cooperation has laid the foundations for the adoption of measures of great importance for a sustainable development that ensures a sustainable future for future generations and a sustainable life based on security. "The Ecological Initiatives and Sustainable Development Group" Foundation has set up the first national and international forums on sustainable development, sustainability and environmental protection. The meetings organized over time have raised interest for collaboration at the level of civil society, academia and socio-political environment. Romania, together with the Member States, respecting the principle of subsidiarity of the European Union, is committed to the implementation of both the 2030 Agenda and the 17 Sustainable Development Goals, as well as the Green Deal Agenda with its 8 major pillars. The strategy aims to prevent and reduce marine pollution, sustainably manage and protect marine ecosystems, conserve coastal areas and ensure sustainable fisheries. To reduce pollution, the 2030 targets are achievable, but stronger action is needed.
Keywords: Q00; Q01; Q58; Q59; 330; cooperation; sustainable development; sustainability; strategies